Increased burden of cardiovascular risk among youth suicide attempters. Issue 10 (19th July 2022) - Zhong, Yongqi; Pham, Steven; Porta, Giovanna; Douaihy, Antoine; Marsland, Anna; Brent, David; Melhem, Nadine M.
Abstract: Background: Suicide and cardiovascular disease rank among the leading causes of disability and premature mortality worldwide. Young adult suicide attempters are at increased risk of mortality from cardiovascular disease even compared to those with major depressive disorder suggesting an increased burden of cardiovascular risk factors. We compared the cardiovascular risk burden between youth attempters and other high-risk individuals. Methods: Participants were from the Collaborative Psychiatric Epidemiology Surveys (CPES), a U.S. population-based study, aged 18–30 years [suicide attempt (SA): n = 303; suicidal ideation (SI): n = 451; controls: n = 3671]; and psychiatric inpatients admitted for a SA ( n = 38) or SI ( n = 40) and healthy controls ( n = 37) aged 15–30 years. We computed a cardiovascular risk score and high- and low-risk latent classes based on risk factors of high blood pressure, obesity, and smoking. Results: Suicide attempters showed an increased cardiovascular risk score (CPES: B = 0.43, 95% confidence interval (CI) 0.31–0.54, p < 0.001; inpatient sample: B = 1.61, 95% CI 0.53–2.68, p = 0.004) compared to controls. They were also more likely to be classified in the high cardiovascular risk group (CPES: odds ratio (OR) 3.36, 95% CI 1.67–6.78, p = 0.001; inpatient sample: OR 9.89, 95% CI 1.38–85.39, p = 0.03) compared to those with SI (CPES: OR 1.15, 95% CI 0.55–2.39, p = 0.71; inpatient sample: OR 1.91, 95% CI 0.25–15.00, p = 0.53). Conclusions: Youth attempters show an increased burden for cardiovascular risk compared to other high-risk individuals in inpatient and population-based samples. Clinicians should pay particular attention to cardiovascular risk factors among suicide attempters in order to reduce their risk for cardiovascular events.